Non-aqueous electrolyte secondary battery
By strategically distributing graphite particles with varying internal gaps in the negative electrode active material layer, the battery addresses resistance issues in low-temperature environments, enhancing its low-temperature performance.
Patent Information
- Application Number
- JP2021502182
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-28
- Filing Date
- 2020-02-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-02-21
AI Technical Summary
Non-hydrogen secondary batteries, such as lithium-ion batteries, experience increased resistance and reduced capacity in low-temperature environments due to the decreased mobility of lithium ions.
The battery design incorporates a negative electrode active material layer with specific distributions of graphite particles A and B, where graphite particles A with an internal gap rate of 8% to 20% are predominantly in the first region, and graphite particles B with an internal gap rate of 5% or less are in the second region, enhancing electrolyte diffusion pathways.
This configuration suppresses the rise in resistance and improves low-temperature performance by maintaining reactivity and increasing electrolyte diffusion, resulting in better low-temperature characteristics.
Smart Images

Figure 0007621243000002 
Figure 0007621243000003 
Figure 0007621243000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, non-aqueous electrolyte secondary batteries such as lithium ion batteries using carbon materials such as graphite as negative electrode active materials have been used as power sources for electric vehicles, etc. For example, Patent Document 1 discloses a non-aqueous electrolyte secondary battery using densified carbon with an internal porosity of 5% or less as the carbon material. In addition, Patent Document 2 discloses a non-aqueous electrolyte secondary battery using a mixture of carbon material A with an internal porosity of 1% or more and less than 23% and carbon material B with an internal porosity of 23% to 40% as the carbon material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-320600 [Patent Document 2] JP 2014-67638 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, when a non-aqueous electrolyte secondary battery is used in a low-temperature environment, for example, the viscosity of the electrolyte increases, causing a decrease in the mobility of lithium ions, resulting in an increase in resistance and a decrease in capacity due to the increase in resistance, etc. An object of the present disclosure is to provide a non-aqueous electrolyte secondary battery having excellent low-temperature characteristics that can suppress an increase in resistance in a low-temperature environment. [Means for solving the problem]
[0005] A nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a negative electrode having a negative electrode current collector and a negative electrode active material layer provided on the negative electrode current collector, the negative electrode active material layer including graphite particles A and graphite particles B as negative electrode active materials, the graphite particles A having an internal porosity of 8% to 20% and the graphite particles B having an internal porosity of 5% or less, and the graphite particles A being contained in a larger amount in a second region that is an outer surface side half of the negative electrode active material layer than in a first region that is an outer surface side half of the negative electrode current collector when the negative electrode active material layer is divided into two equal parts in a thickness direction. Effect of the Invention
[0006] According to the nonaqueous electrolyte secondary battery according to the present disclosure, an increase in resistance in a low-temperature environment is suppressed, and therefore the nonaqueous electrolyte secondary battery according to the present disclosure has excellent low-temperature characteristics. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of a negative electrode according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of a graphite particle in a negative electrode active material layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] As described above, it is an important issue to suppress the increase in resistance of a non-aqueous electrolyte secondary battery in a low-temperature environment and to suppress the decrease in output characteristics, charge capacity, discharge capacity, etc., caused by the increase in resistance. As a result of intensive research to solve this issue, the present inventors have found that the increase in resistance in a low-temperature environment is suppressed and the low-temperature characteristics are improved by having more graphite particles A with an internal porosity of 8% to 20% in the second region, which is the outer surface side half of the negative electrode active material layer, than in the first region, which is the negative electrode current collector side half of the negative electrode active material layer. In addition, it is preferable that more graphite particles B with an internal porosity of 5% or less are contained in the first region of the negative electrode active material layer than in the second region.
[0009] The graphite particles A have a larger specific surface area than graphite particles with a smaller internal porosity. Therefore, by using the graphite particles A, the decrease in the reactivity of the negative electrode can be suppressed. On the other hand, the graphite particles A are more easily deformed when the negative electrode is compressed than the graphite particles with a smaller internal porosity, and in the region containing a large amount of the graphite particles A, the gaps between the particles become smaller and the diffusion path of the electrolyte decreases. Therefore, in the first region of the negative electrode active material layer, where the electrolyte is difficult to penetrate, the decrease in the conductivity of lithium ions in a low-temperature environment becomes significant. In other words, by reducing the content of the graphite particles A in the first region of the negative electrode active material layer, the gaps in the negative electrode active material layer can be increased to increase the diffusion path of the electrolyte.
[0010] In the nonaqueous electrolyte secondary battery according to the present disclosure, the graphite particles A are present in a larger amount in the second region than in the first region of the negative electrode active material layer, i.e., the content of the graphite particles A is lower in the first region than in the second region. This makes it possible to increase the diffusion paths of the electrolyte in the first region while suppressing a decrease in the reactivity of the negative electrode surface even in a low-temperature environment. Therefore, the nonaqueous electrolyte secondary battery according to the present disclosure has excellent low-temperature characteristics.
[0011] Hereinafter, an example of an embodiment will be described in detail with reference to the drawings. Note that the nonaqueous electrolyte secondary battery of the present disclosure is not limited to the embodiment described below. Also, the drawings referred to in the description of the embodiment are schematic.
[0012] FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment. The nonaqueous electrolyte secondary battery 10 shown in FIG. 1 includes a wound electrode assembly 14 formed by winding a positive electrode 11 and a negative electrode 12 with a separator 13 interposed therebetween, a nonaqueous electrolyte, insulating plates 18 and 19 respectively arranged above and below the electrode assembly 14, and an exterior can 16 for accommodating the above-mentioned components. The exterior can 16 is a cylindrical metal container with a bottom, and its opening is sealed by a sealing body 17. Note that, instead of the wound electrode assembly 14, an electrode assembly of another form may be applied, such as a laminated electrode assembly formed by alternately stacking positive and negative electrodes with a separator interposed therebetween. In addition, the battery case may be a rectangular, coin-shaped, button-shaped, or other metal exterior can, or a pouch exterior body formed by laminating a resin sheet and a metal sheet.
[0013] As described above, the exterior can 16 is a cylindrical metal container with a bottom. A gasket 28 is provided between the exterior can 16 and the sealing body 17 to ensure airtightness inside the battery. The exterior can 16 has a grooved portion 22 that supports the sealing body 17, for example, a part of the side surface of the exterior can 16 protruding inward. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface.
[0014] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective centers, and the insulating member 25 is interposed between each of their peripheral edges. When the internal pressure of the nonaqueous electrolyte secondary battery 10 increases due to heat generation caused by an internal short circuit or the like, for example, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, and the current path between the lower valve body 24 and the upper valve body 26 is interrupted. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0015] 1, a positive electrode lead 20 attached to a positive electrode 11 passes through a through hole in an insulating plate 18 and extends toward a sealing body 17, and a negative electrode lead 21 attached to a negative electrode 12 passes outside an insulating plate 19 and extends toward the bottom side of an outer can 16. The positive electrode lead 20 is connected to the underside of an internal terminal plate 23, which is the bottom plate of the sealing body 17, by welding or the like, and a cap 27, which is the top plate of the sealing body 17 and is electrically connected to the internal terminal plate 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom surface of the outer can 16 by welding or the like, and the outer can 16 serves as a negative electrode terminal.
[0016] Each of the components of the nonaqueous electrolyte secondary battery 10 will be described in detail below.
[0017] [Negative electrode] 2 is a cross-sectional view of a negative electrode according to an embodiment of the present invention. The negative electrode 12 has a negative electrode current collector 40 and a negative electrode active material layer 42 provided on the surface of the negative electrode current collector 40. The negative electrode active material layer 42 is preferably provided on both sides of the negative electrode current collector 40.
[0018] The negative electrode current collector 40 may be, for example, a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film having such a metal disposed on its surface.
[0019] The negative electrode active material layer 42 contains graphite particles as the negative electrode active material. The negative electrode active material layer 42 preferably contains a binder and the like. The negative electrode 12 can be produced, for example, by preparing a negative electrode mixture slurry containing a negative electrode active material, a binder, and the like, applying the negative electrode mixture slurry onto the negative electrode current collector 40, drying the slurry to form the negative electrode active material layer 42, and rolling the negative electrode active material layer 42. The method for producing the negative electrode active material layer 42 will be described in detail later.
[0020] Fig. 3 is a cross-sectional view of a graphite particle in a negative electrode active material layer. As shown in Fig. 3, a graphite particle 30 has, in a cross-sectional view of the graphite particle 30, closed voids 34 that do not connect the inside of the particle to the particle surface (hereinafter, internal voids 34) and voids 36 that connect the inside of the particle to the particle surface (hereinafter, external voids 36).
[0021] The volume-based median diameter (hereinafter, "D50") of the graphite particles 30 is, for example, 5 μm to 30 μm, and preferably 10 μm to 25 μm. D50 can be measured using a laser diffraction particle size distribution measuring device (for example, HORIBA's LA950) with water as a dispersion medium. D50 refers to the particle diameter of the smallest cumulative 50% in the volume-based particle size distribution.
[0022] The graphite particles 30 in this embodiment include graphite particles A having an internal porosity of 8% to 20% and graphite particles B having an internal porosity of 5% or less. The internal porosity of the graphite particles A may be 8% to 20% in order to suppress an increase in resistance in a low-temperature environment, but is preferably 10% to 18%, and more preferably 12% to 16%. The internal porosity of the graphite particles B may be 5% or less in order to suppress an increase in resistance in a low-temperature environment, but is preferably 1% to 5%, and more preferably 3% to 5%. Here, the internal porosity of the graphite particles is a two-dimensional value calculated from the ratio of the area of the internal voids 34 of the graphite particles to the cross-sectional area of the graphite particles. The internal porosity of the graphite particles is calculated by the following procedure.
[0023] <Method for measuring internal porosity> (1) Exposing a cross section of the negative electrode active material layer. For example, a method for exposing the cross section includes cutting out a part of the negative electrode and processing it with an ion milling device (e.g., IM4000PLUS manufactured by Hitachi High-Technologies Corporation) to expose the cross section of the negative electrode active material layer. (2) A backscattered electron image of the cross section of the exposed negative electrode active material layer is taken using a scanning electron microscope at a magnification of 3,000 to 5,000 times. (3) The cross-sectional image obtained as described above is imported into a computer and binarized using image analysis software (e.g., ImageJ, manufactured by the National Institutes of Health, USA) to obtain a binary processed image in which the particle cross-sections in the cross-sectional image are colored black and voids present in the particle cross-sections are colored white. (4) From the binarized image, graphite particles A and B with particle sizes of 5 μm to 50 μm are selected, and the area of the graphite particle cross section and the area of the internal voids present in the graphite particle cross section are calculated. Here, the area of the graphite particle cross section refers to the area of the region surrounded by the outer periphery of the graphite particle, i.e., the area of the entire cross section of the graphite particle. Furthermore, for voids present in the graphite particle cross section that are 3 μm or less in width, it may be difficult to distinguish whether they are internal or external voids in image analysis, so voids with a width of 3 μm or less may be considered internal voids. Then, from the calculated graphite particle cross section area and the area of the internal voids in the graphite particle cross section, the internal porosity of the graphite particle (area of internal voids in graphite particle cross section × 100 / graphite particle child The internal porosity of graphite particles A and B is the average value of 10 graphite particles A and B.
[0024] The graphite particles A and B are produced, for example, as follows. <Graphite particles A with internal porosity of 8% to 20%> For example, the coke (precursor) as the main raw material is crushed to a predetermined size, aggregated with a binder, and then pressed into a block shape, which is then fired at a temperature of 2600°C or higher to be graphitized. The graphitized block-shaped body is crushed and sieved to obtain graphite particles A of a desired size. Here, the internal porosity can be adjusted to 8% to 20% depending on the amount of volatile components added to the block-shaped body. The D50 of the precursor after crushing is preferably in the range of 12 μm to 20 μm. When a part of the binder added to the coke (precursor) volatilizes during firing, the binder can be used as a volatile component. Pitch is an example of such a binder.
[0025] <Graphite particles B with internal porosity of 5% or less> For example, the coke (precursor) as the main raw material is crushed to a predetermined size, and then the crushed coke is agglomerated with a binder, baked at a temperature of 2600°C or higher, graphitized, and sieved to obtain graphite particles B of a desired size. Here, the internal porosity can be adjusted to 5% or less depending on the particle size of the crushed precursor or the particle size of the agglomerated precursor. The D50 of the crushed precursor is preferably in the range of 12 μm to 20 μm. In addition, when the internal porosity is reduced to a range of 5% or less, it is preferable to increase the particle size of the crushed precursor.
[0026] The graphite particles A and B used in this embodiment may be natural graphite, artificial graphite, or the like, but are not particularly limited thereto. However, in terms of ease of adjusting the internal porosity, artificial graphite is preferred. The interplanar spacing (d 002 ) is, for example, preferably 0.3354 nm or more, more preferably 0.3357 nm or more, and preferably less than 0.340 nm, more preferably 0.338 nm or less. The crystallite size (Lc(002)) of the graphite particles A and B used in this embodiment, determined by X-ray diffraction, is, for example, preferably 5 nm or more, more preferably 10 nm or more, and preferably 300 nm or less, more preferably 200 nm or less. The interplanar spacing (d 002 When the crystallite size (Lc(002)) satisfies the above range, the battery capacity of the nonaqueous electrolyte secondary battery tends to be larger than when the crystallite size (Lc(002)) does not satisfy the above range.
[0027] In this embodiment, the graphite particles A are contained in a larger amount in the second region 42B, which is the outer surface half, than in the first region 42A, which is the negative electrode current collector half, when the negative electrode active material layer 42 shown in FIG. 2 is divided in half in the thickness direction. This makes it possible to increase the diffusion paths of the electrolyte in the first region 42A, into which the electrolyte is less likely to penetrate, while suppressing a decrease in the reactivity of the negative electrode 12. This suppresses an increase in resistance in a low-temperature environment, improving the low-temperature characteristics of the battery. Note that dividing the negative electrode active material layer 42 in the thickness direction means dividing the negative electrode active material layer 42 in half at the middle Z of the thickness of the negative electrode active material layer 42 when the stacking direction of the negative electrode current collector 40 and the negative electrode active material layer 42 is the thickness direction of the negative electrode active material layer 42. The negative electrode active material layer 42 is divided into two equal parts in the thickness direction, and the negative electrode active material layer 42 located closer to the negative electrode current collector 40 is designated as the first region 42A of the negative electrode current collector side half, and the negative electrode active material layer 42 located farther from the negative electrode current collector 40 is designated as the second region 42B of the outer surface side half.
[0028] It is sufficient that the graphite particles A are contained more in the second region 42B than in the first region 42A, and the graphite particles A may be contained only in the second region 42B. In order to further suppress an increase in resistance in a low-temperature environment, the graphite particles B are preferably contained more in the first region 42A than in the second region 42B, and the graphite particles B may be contained only in the first region 42A. That is, the content of the graphite particles A is first region 42A<second region 42B, and the content of the graphite particles B is first region 42A>second region 42B.
[0029] The ratio by mass of the graphite particles A and the graphite particles B in the second region 42B is preferably 50:50 to 100:0, and more preferably 75:25 to 100:0. The ratio by mass of the graphite particles A and the graphite particles B in the first region 42A is preferably 25:75 to 0:100, and more preferably 10:90 to 0:100.
[0030] A specific method for making the amount of graphite particles A larger in the second region 42B than in the first region 42A will be described. For example, first, a negative electrode active material containing graphite particles B (graphite particles A as necessary), a binder, and a solvent such as water are mixed to prepare a negative electrode mixture slurry for the first region. Separately, a negative electrode active material containing a larger amount of graphite particles A (graphite particles B as necessary) than the negative electrode mixture slurry for the first region is mixed with a binder and a solvent such as water to prepare a negative electrode mixture slurry for the second region. Then, the negative electrode mixture slurry for the first region is applied to both sides of the negative electrode current collector and dried, and then the negative electrode mixture slurry for the second region is applied to both sides of the coating film of the negative electrode mixture slurry for the first region and dried, thereby forming the negative electrode active material layer 42. In the above method, the negative electrode mixture slurry for the first region is applied and dried, and then the negative electrode mixture slurry for the second region is applied. However, a method in which the negative electrode mixture slurry for the second region is applied after the negative electrode mixture slurry for the first region and before drying may be used.
[0031] The negative electrode active material may contain, in addition to the graphite particles A and B used in this embodiment, other materials capable of reversibly absorbing and releasing lithium ions, for example, a Si-based material. Examples of the Si-based material include Si, an alloy containing Si, and SiO x (x is 0.8 to 1.6) and the like. Si-based materials are anode materials that can improve battery capacity more than graphite particles, but on the other hand, they are disadvantageous in terms of cycle characteristics because of their large volume expansion during charging and discharging. The content of the Si-based material is, for example, preferably 1 mass % to 10 mass %, and more preferably 3 mass % to 7 mass %, relative to the mass of the anode active material, from the viewpoints of improving battery capacity and suppressing deterioration of cycle characteristics.
[0032] Other examples of the other material capable of reversibly absorbing and releasing lithium ions include metals that are alloyed with lithium, such as tin (Sn), or alloys or oxides containing metal elements such as Sn. The negative electrode active material may contain the other materials, and the content of the other materials is desirably, for example, 10% by mass or less with respect to the mass of the negative electrode active material.
[0033] Examples of the binder include fluorine-based resins, PAN, polyimide-based resins, acrylic-based resins, polyolefin-based resins, styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or a salt thereof, polyacrylic acid (PAA) or a salt thereof (PAA-Na, PAA-K, etc., or a partially neutralized salt), polyvinyl alcohol (PVA), etc. These may be used alone or in combination of two or more.
[0034] [Positive electrode] The positive electrode 11 is composed of a positive electrode current collector such as a metal foil and a positive electrode active material layer provided on the surface of the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum that is stable in the potential range of the positive electrode, or a film having such a metal disposed on the surface layer. The positive electrode active material layer contains, for example, a positive electrode active material, a binder, a conductive agent, etc.
[0035] The positive electrode 11 can be produced, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive agent, etc. onto a positive electrode current collector, drying it to form a positive electrode active material layer, and then rolling this positive electrode active material layer.
[0036] The positive electrode active material may be, for example, a lithium-containing transition metal composite oxide containing a transition metal element such as Co, Mn, or Ni. x CoO2, Li x NiO2, Li x MnO2, Li x Co y Ni 1-y O2, Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4, Li x Mn 2-y M yO4, LiMPO4, Li2MPO4F (M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B; 0 < x ≤ 1.2, 0 < y ≤ 0.9, 2.0 ≤ z ≤ 2.3). These may be used alone or in combination of multiple kinds. In terms of achieving high capacity of the non-aqueous electrolyte secondary battery, the cathode active material is Li x NiO2, Li x Co y Ni 1-y O2, Li x Ni 1-y M y O z (M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B; 0 < x ≤ 1.2, 0 < y ≤ 0.9, 2.0 ≤ z ≤ 2.3), etc. lithium nickel composite oxides are preferably included.
[0037] Examples of the conductive agent include carbon-based particles such as carbon black (CB), acetylene black (AB), ketjen black, and graphite. These may be used alone or in combination of two or more kinds.
[0038] Examples of the binder include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide-based resins, acrylic-based resins, and polyolefin-based resins. These may be used alone or in combination of two or more kinds.
[0039] [Separator] For example, a porous sheet having ion permeability and insulation is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The separator is preferably made of an olefin resin such as polyethylene or polypropylene, or cellulose. The separator 13 may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. Alternatively, the separator may be a multilayer separator including a polyethylene layer and a polypropylene layer, and a separator having a surface coated with a material such as an aramid resin or ceramic may be used.
[0040] [Non-aqueous electrolyte] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte is not limited to a liquid electrolyte (electrolytic solution), and may be a solid electrolyte using a gel-like polymer or the like. The non-aqueous solvent may be, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, or a mixed solvent of two or more of these. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is substituted with a halogen atom such as fluorine.
[0041] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone and γ-valerolactone; methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate. Le et al. and chain carboxylates of the formula:
[0042] Examples of the above-mentioned ethers include cyclic ethers such as 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, crown ether, etc., and chain ethers such as 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and chain ethers such as those mentioned above can be cited.
[0043] As the above-mentioned halogenated compounds, it is preferable to use fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylic acid esters such as methyl fluoropropionate (FMP), etc.
[0044] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (CnF 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10, LiCl, LiBr, LiI, lithium chloroborane, lower aliphatic lithium carboxylates, Li2B4O7, Li(B(C2O4)F2) and other borates, LiN(SO2CF3)2, LiN(C l F2 l+1 SO2)(C m F 2m+1 Examples of the lithium salt include imide salts such as LiPF6, LiPF2, and LiPF6 (where l and m are integers of 1 or more). The lithium salt may be used alone or in combination. Among these, LiPF6 is preferably used from the viewpoints of ion conductivity, electrochemical stability, and the like. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of the solvent. EXAMPLES
[0045] The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.
[0046] <Example 1> [Preparation of positive electrode] As the positive electrode active material, LiNi 0.91 Co 0.45 Al 0.45 A lithium-containing transition metal composite oxide represented by O2 was used. 100 parts by mass of the positive electrode active material, 1 part by mass of graphite as a conductive agent, and 0.9 parts by mass of polyvinylidene fluoride powder as a binder were mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to prepare a positive electrode mixture slurry. This slurry was applied to both sides of a positive electrode current collector made of aluminum foil (thickness 15 μm) by the doctor blade method, and after drying the coating film, the coating film was rolled with a rolling roller to prepare a positive electrode in which a positive electrode active material layer was formed on both sides of the positive electrode current collector. In addition, an exposed portion where the collector surface was exposed was provided in the longitudinal center of the positive electrode, and an aluminum positive electrode lead was attached to the exposed portion.
[0047] [Preparation of graphite particles A] The coke was crushed until the D50 became 15μm, and the crushed coke was agglomerated by adding pitch as a binder. Then, the coke was subjected to an isostatic pressure of 1.6g / cm 3 ~1.9g / cm3 A block-shaped compact having a density of 1000 nm was produced. This block-shaped compact was graphitized by firing at a temperature of 2800° C. Next, the graphitized block-shaped compact was pulverized and sieved using a 250 mesh sieve to obtain graphite particles A having a D50 of 23 μm.
[0048] [Preparation of graphite particles B] Pitch was added as a binder to the crushed coke, and the mixture was aggregated until the D50 became 15 μm. The aggregate was graphitized by baking at a temperature of 2800° C., and then sieved using a 250 mesh sieve to obtain graphite particles B having a D50 of 17 μm.
[0049] [Preparation of negative electrode] Graphite particles A were mixed to 95 parts by mass, and particles of a Si-containing compound represented by SiO in which Si particles are dispersed in SiO2 were mixed to 5 parts by mass, and this was used as the negative electrode active material A contained in the second region of the outer surface half of the negative electrode active material layer. These were mixed so that the mass ratio of negative electrode active material A: carboxymethylcellulose (CMC): styrene-butadiene copolymer rubber (SBR) was 100:1:1 to prepare a negative electrode mixture slurry A. In addition, graphite particles B were mixed to 95 parts by mass, and SiO was mixed to 5 parts by mass, and this was used as the negative electrode active material B contained in the first region of the negative electrode current collector half of the negative electrode active material layer. These were mixed so that the mass ratio of negative electrode active material B: carboxymethylcellulose (CMC): styrene-butadiene copolymer rubber (SBR) was 100:1:1 to prepare a negative electrode mixture slurry B.
[0050] The negative electrode mixture slurry B was applied to both sides of a negative electrode current collector made of copper foil by the doctor blade method, and the coating film was dried. The negative electrode mixture slurry A was applied to the coating film, and after drying, the coating film was rolled with a rolling roller to produce a negative electrode in which a negative electrode active material layer was formed on both sides of the negative electrode current collector. That is, the graphite particles A:graphite particles B in the second region of the negative electrode active material layer were 100:0 in mass ratio, and the graphite particles A:graphite particles B in the first region of the negative electrode active material layer were 0:100 in mass ratio. In addition, when the internal porosity of the graphite particles A and B in the produced negative electrode was measured, it was 15% and 3%, respectively. The measurement method is as described above, so it is omitted. An exposed portion where the current collector surface was exposed was provided at one end in the longitudinal direction of the negative electrode, and a negative electrode lead made of nickel / copper / nickel was attached to the exposed portion.
[0051] [Preparation of non-aqueous electrolyte] A non-aqueous electrolyte solution was prepared by adding vinylene carbonate (VC) at a concentration of 5 mass% to a non-aqueous solvent made by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 4:1:15, and dissolving LiPF6 at a concentration of 1.35 mol / L.
[0052] [Cylindrical battery construction] The positive electrode and the negative electrode were wound in a spiral shape with a polyethylene separator interposed therebetween to produce a wound electrode body. Insulating plates were placed on the top and bottom of the electrode body, respectively, the negative electrode lead was welded to the inner bottom surface of the outer can, and the positive electrode lead was welded to a sealing body, and the electrode body was housed in the outer can. Thereafter, a nonaqueous electrolyte was injected into the outer can, and the opening of the outer can was sealed with a sealing body via a gasket to produce a cylindrical battery. The capacity of the battery was 4700mAh.
[0053] <Example 2> A negative electrode was produced in the same manner as in Example 1, except that a mixture of graphite particles A and graphite particles B mixed in a mass ratio of 75:25 was mixed to give 95 parts by mass and 5 parts by mass of SiO, and this was used as negative electrode active material A. That is, the mass ratio of graphite particles A:graphite particles B in the second region of the negative electrode active material layer was 75:25. Using this as the negative electrode of Example 2, a cylindrical battery was produced in the same manner as in Example 1.
[0054] <Example 3> A negative electrode was produced in the same manner as in Example 1, except that a mixture of graphite particles A and graphite particles B mixed in a mass ratio of 25:75 was mixed to give 95 parts by mass and 5 parts by mass of SiO, and this was used as negative electrode active material B. That is, the mass ratio of graphite particles A:graphite particles B in the first region of the negative electrode active material layer was 25:75. Using this as the negative electrode of Example 3, a cylindrical battery was produced in the same manner as in Example 1.
[0055] <Comparative Example 1> A coating film was formed on both sides of a negative electrode current collector using the negative electrode mixture slurry A, and then a coating film was formed using the negative electrode mixture slurry B to form a negative electrode active material layer in which the mass ratio of graphite particles A:graphite particles B in the second region was 0:100 and the mass ratio of graphite particles A:graphite particles B in the first region was 100:0. Except for this, a negative electrode and a cylindrical battery were produced in the same manner as in Example 1.
[0056] <Comparative Example 2> A negative electrode and a cylindrical battery were produced in the same manner as in Example 1, except that a mixture of 95 parts by mass of graphite particles A and 5 parts by mass of SiO was used as negative electrode active materials A and B, in which graphite particles A and graphite particles B were mixed in a mass ratio of 50:50.
[0057] <Comparative Example 3> A negative electrode and a cylindrical battery were produced in the same manner as in Example 1, except that only the negative electrode mixture slurry A was used to form the negative electrode active material layer.
[0058] <Comparative Example 4> A negative electrode and a cylindrical battery were produced in the same manner as in Example 1, except that only the negative electrode mixture slurry B was used to form the negative electrode active material layer.
[0059] [Evaluation of low-temperature characteristics] Each battery of the examples and comparative examples was charged at a constant current of 0.3 C (1 C = 4700 mA) at 25° C. up to a battery voltage of 3.54 V, and then charged at a constant voltage of 1 / 50 C. After resting for 2 hours in an environment of −20° C., each battery was charged and discharged at 0.3 C, and the direct current resistance (DCR) was measured. The evaluation results are shown in Table 1. DCR(Ω)=(Voltage after 10 seconds - Initial voltage) / Current
[0060] [Table 1]
[0061] As can be seen from Table 1, all of the batteries of the examples had lower low-temperature DCR values compared to the batteries of the comparative examples. In the batteries of the examples, the graphite particles A were abundant in the second region of the negative electrode active material layer that contacted the electrolyte, and the graphite particles B were abundant in the first region into which the electrolyte is less likely to penetrate. This is believed to have suppressed the decrease in the reactivity of the negative electrode while increasing the diffusion path of the electrolyte in the first region, thereby suppressing the increase in resistance.
[0062] It is believed that the low-temperature DCR increased in the batteries of Comparative Examples 1 and 2 due to the decrease in the reactivity of the negative electrode and the insufficient formation of a diffusion path for the electrolyte in the first region of the negative electrode active material layer. It is believed that the low-temperature DCR increased in the battery of Comparative Example 3 due to the insufficient formation of a diffusion path for the electrolyte in the first region of the negative electrode active material layer, and in the battery of Comparative Example 4 due to the decrease in the reactivity of the negative electrode. [Explanation of symbols]
[0063] REFERENCE SIGNS LIST 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 grooved portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cap, 28 gasket, 30 graphite particles, 34 internal gap, 36 external gap, 40 negative electrode current collector, 42 negative electrode active material layer, 42A first region, 42B second region
Claims
1. a negative electrode including a negative electrode current collector and a negative electrode active material layer provided on the negative electrode current collector; The negative electrode active material layer contains graphite particles A and graphite particles B as negative electrode active materials, the graphite particles A have an internal porosity of 8% to 20%, and the graphite particles B have an internal porosity of 5% or less; the graphite particles A are contained in a larger amount in a second region, which is a half of the negative electrode active material layer on the outer surface side, than in a first region, which is a half of the negative electrode current collector side, when the negative electrode active material layer is divided into two equal parts in a thickness direction; a mass of the graphite particles A is greater than a mass of the graphite particles B in the second region.
2. The nonaqueous electrolyte secondary battery according to claim 1 , wherein the graphite particles B are contained in a larger amount in the first region than in the second region.
3. 3. The nonaqueous electrolyte secondary battery according to claim 1, wherein a ratio of the graphite particles A to the graphite particles B in the second region is 75:25 to 100:0 in terms of mass ratio.
4. 4. The nonaqueous electrolyte secondary battery according to claim 1, wherein the negative electrode active material includes a Si-based material.
Citation Information
Patent Citations
Cathode material of lithium ion battery and preparation method thereof
CN103199251A
Electrochemical battery fined carbon
JP1997320600A
Carbon material for nonaqueous secondary battery, negative electrode, and nonaqueous secondary battery
JP2014067638A
Nonaqueous electrolyte secondary battery
JP2015133296A
Negative electrode for lithium ion secondary battery
JP2018125077A